Clival and Paraclival Lesions: A Pictorial Review - Palsetia, Delnaz R.; Vijan, Antariksh V.; Gala, Foram B.; Sahu, Amit C.; Patkar, Deepak P.; A., Arpita Sahu (Indian Journal of Radiology and Imaging, 2023)
The clivus is a midline anatomical structure in the central skull base. It is affected by a wide range of non-neoplastic, benign and malignant pathologies, some of which typically affect the clivus because of its strategic location and embryological origins. Clival lesions may often be asymptomatic with occasional complaints like headache or cranial neuropathy in few. Cross-sectional imaging techniques, namely, computed tomographic scan and magnetic resonance imaging, thus, play a key role in approximating to the final diagnosis and estimating the disease extent. In this article, we highlight the important imaging features of various clival and paraclival pathologies to facilitate effective diagnosis, therapeutic planning, and management.
Keywords: magnetic resonance imaging; skull base; clivus; abducens nerve; skull base neoplasms/complications